Influência do aquecimento e armazenamento de ovos de matrizes pesadas sobre o rendimento de incubação - Paula Moraes Mour?o Mendes (2012)
This study aimed to evaluate the effects of prestorage incubation of broiler breeder´s eggs on hatchability. Two experiments were conducted. In Experiment I, were used 5,760 eggs from Cobb ® hens, 57 weeks old. The experimental design was completely randomized, with four treatments based on egg´s heating time (zero, three, six or nine hours). Heating was done in a fumigation chamber at 30 ° C and the eggs were stored for three days. In Experiment II, were used 11,520 eggs from Cobb ® hens, 32 weeks old. The experimental design was completely randomized in a factorial 2 × 4, two storage periods (three or seven days) and four heating times (zero, three, six or nine hours). Egg´s heating was done in fumigation chamber at 37.5 ° C. Treatments didn´t affect hatchability and embryonic mortality in both experiments. In Experiment II, prestorage incubation and storage reduced chick weight.